Socio-Economic and Environmental Risk Factors of Tuberculosis in Wonosobo, Central Java, Indonesia (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
This study discusses the dominant socio-economic and environmental risk factors for TB disease. The design of this study was a case-control study with 70 case samples and control with a contribution of n = 1. Variables from this study contacted personal, ventilation of the house, humidity, the temperature of the house, density of the house, kitchen, and family earnings. Multivariate data analysis uses multiple logistic regressions. The study notes that from 140 samples, 47% have basic education, and 30% are farmers. People who had a past of contact with TB cases were ten times more likely to contract TB than those who had no contacted (OR = 10.00; p 0.001). Personalities who live in poorly ventilated homes who have a risk of contracting TB are 2.2 times greater than those who live in homes with standard ventilation (OR = 2.20; p 0.018). The moisture increases the risk of TB by four times the low moisture (OR = 4.00; p = 0.001). Living in a house with a higher temperature of TB is 3.8 times higher than a lower temperature (OR = 3.80; p = 0.009). Living in a high population density of the house improves TB five times more than living in a lesser home (OR = 5.00; p 0.001). Kitchen gas enhances the risk of TB 2.5 times greater than gasless (OR = 2.50; p = 0.007). Low family earnings raise the risk of TB three times greater than high family earnings (OR = 3.00; p = 0.002). A past of contact, poorly ventilated homes, high humidity, hothouse temperature, population density, kitchen gas, and low family earnings, are risk factors for TB in Wonosobo, Central Java.